2007
DOI: 10.4269/ajtmh.2007.76.886
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis in Fatal Anicteric Leptospirosis

Abstract: We report a fatal case of anicteric leptospirosis with pancreatitis (acute hyperglycemia and insulin requirement, elevated lipase and amylase levels), pulmonary infiltrates, and refractory shock. In disease-endemic areas, leptospirosis with pancreatitis should be considered in patients with fever and abdominal pain, and serum pancreatic enzymes, blood glucose, and serum electrolytes should be closely monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
(15 reference statements)
0
15
0
5
Order By: Relevance
“…2 Pancreatitis is described as an uncommon complication of leptospirosis, but there are a considerable number of reports in literature. [37][38][39][40] In the present study, the complications found were pulmonary bleeding (14%), tract intestinal bleeding (13%), atrial fibrillation (11.4%), pulmonary infection (6.0%), meningitis (1.0%) and pancreatitis (0.5%).…”
Section: Discussionmentioning
confidence: 99%
“…2 Pancreatitis is described as an uncommon complication of leptospirosis, but there are a considerable number of reports in literature. [37][38][39][40] In the present study, the complications found were pulmonary bleeding (14%), tract intestinal bleeding (13%), atrial fibrillation (11.4%), pulmonary infection (6.0%), meningitis (1.0%) and pancreatitis (0.5%).…”
Section: Discussionmentioning
confidence: 99%
“…(27,36). Patients suffering from leptospirosis have a diverse array of clinical symptoms, such as meningitis (10), pneumonitis (12), hepatitis (1), nephritis (31), and pancreatitis (35), and death may result (5). It is known that zoonotic infections of humans with leptospires are a significant public health problem in developing countries (24).…”
Section: ؉ T Lymphocytes Derived From Lipl21-or Lipl32-immunized Balbmentioning
confidence: 99%
“…The disease can occur in two forms: Anicteric leptospirosis [3] and severe leptospirosis called Weil's Syndrome.…”
Section: Discussionmentioning
confidence: 99%